Value Creation Strategy through a Conceptual KPI-based Framework of Performance Management in the Romanian Agri-food Industry - Marius CONSTANTIN; Raluca IGNAT; Raluca Mihaela DRACEA; Bogdan Cristian CHIRIPUCI (Communications of International Proceedings, 2021)
Improving the value creation process in the Romanian agri-food industry is one of the critical priorities for the Romanian economy, especially in the context of the post-2020 Common Agricultural Policy and of the new paradigm of an environmentally friendly, highly efficient and circular agri-food system in the European Union. Monitoring and improving the performance of such a complex system has been debated in the literature, yet not many papers approach the topic of value creation through specific performance management instruments – a KPI-based framework, for example. Performance measurement and metrics are crucial to enhance effectiveness and efficiency, which is why improving the value creation process needs to be addressed corroborated with performance management – and not only in the case for the agri-food chains alone. In this context, decision makers are responsible for acting according to the factors that ensure the maximizing value creation process in the Romanian agri-food industry – they should be guilded by a critical KPIs infrastructure that can significantly contribute to the generation of the maximum potential added-value along the chain. Decision makers should strive to improve these results. Taking this into account, the objective of this research paper was to design a conceptual KPI-based framework of performance management for optimizing the value creation process, as well as for enhancing the results obtained by the Romanian agri-food industry. The results of this research can help decision makers to harness Romania’s agricultural potential through the implementation of an instrument specific to performance management.
Keywords: performance management; KPI; value creation; agri-food industry